Effects of ergonomic training and equipment on musculoskeletal system disorders and quality of life in healthcare professionals - Kersu, Ozlem; Kosgeroglu, Nedime (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the association of musculoskeletal disorders with ergonomic training and equipment with respect to the quality of life of nurses working in the intensive care unit. Method: The experimental study was conducted at Eskisehir Osmangazi University Health, Practice and Research Hospital from November 2018 to December 2019, and comprised adult intensive care unit nurses. The nurses were provided with ergonomic equipment (rollboards) to facilitate the transfer patients from bed to stretcher and from stretcher to bed. The nurses were trained on the use of rollboards for a month. Data was collected at baseline and after the training using a personal data collection form, Cornell Musculoskeletal Discomfort Questionnaire, Rapid Entire Body Assessment, and Short Form-36. Data was analysed using SPSS 21. Results: Of the 103 nurses, 71(58.9%) were females and 32(31.1%) were males. There were 30(29.1%) subjects aged 25-29 years, and body mass index was <25kg/m2 in 62(60.2%). Median risk score for lower back was 3.50 (interquartile range: 1.50-14.00; Z=-2.58, p=0.01) and for risky working posture it was 5.00 (interquartile range: 5.00-7.00; Z=-8.39, p<0.001) of nurses which decreased after training and the use of equipment. The sub-dimension scores of the quality of life for the physical function, mental health, social function, general health perception and pain decreased post-intervention, but the difference was not significant (p>0.05). Conclusion: Nurses' musculoskeletal symptoms decreased as a result of ergonomic training and equipment use. Although ergonomic training and equipment use did not affect nurses' quality of life, the ergonomic workplace increased their awareness of ergonomic risk assessment. Key Words: Education, Ergonomics, Musculoskeletal system, Nurses, Quality of life.